(Dis)Embodied Disclosure in Higher Education: A Co-Constructed Narrative - Aubrecht, Katie; La Monica, Nancy (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2017)
In this paper we use co-constructed autoethnographic methods to explore the tensions that animate the meaning of “disclosure” in university and college environments. Drawing insight from our embodied experiences as graduate students and university/college course instructors, our collaborative counter-narratives examine the ordinary ways that disclosure is made meaningful and material as a relationship and a form of embodied labour. Our dialogue illustrates the layered nature of disclosure—for example, self-disclosing as a disabled student in order to access academic spaces but not self-disclosing to teach as an instructor. Katie uses phenomenological disability studies to analyze disclosure at the intersection of disability and pregnancy as body-mediated moments (Draper, 2002). Nancy uses Hochschild’s (1983) notion of “emotional labour” to explore how socio-spatial processes of disclosure can be an embodied form of “extra work” (e.g., managing perceptions of stigmatized identities).